“NATIONAL VALUES REFLECTED IN PHRASEOLOGICAL UNITS: A LINGUISTIC AND CULTURAL ANALYSIS” (Ustozlar uchun, 2025)
Abstract The article considers phraseological units as linguistic and cultural phenomena that reflect the system of national values, worldview, and cultural traditions of a people. A comparative analysis of phraseological units demonstrating the connection between language and culture is conducted, and the peculiarities of their functioning in the context of the national worldview are identified. Particular attention is paid to the ways of expressing mentality, historical experience, and ethnocultural stereotypes encoded in phraseological units.